Quantifying consensus on women's roles using fuzzy logic / Puzziawati Ab Ghani and Abdul Aziz Jemain - Ab Ghani, Puzziawati; Jemain, Abdul Aziz (Fakuiti Teknologi Maklumat dan Sains Kuantitatif, 2005)
With greater access to education and rapid economic development coupled with higher costs of living especially in the urban areas, women are left with no choice but to look for and remain in employment. Women in urban society face more challenges in lives and shoulder multiple roles. The juggling act of balancing between work and family commitments that results in role conflict often drives women to favour one role over the other. What women put as their priority is crucial to the smooth running of family institution, which serves as a basic aspect of family happiness in securing the quality of life. This paper attempts to elucidate what are in the minds of working women when they make decision by investigating the consensus on their role priority. A fuzzy logic approach based on a fuzzy majority concept is employed. The data used are based on a case study among women academicians and supporting staff of Universiti Teknologi MARA in Shah Alam. The study shows that women's role priority still lies within the family domain/sphere.